Rotating- and translating-coil magnetometers for extracting pseudo-multipoles in accelerator magnets. Issue 5 (4th September 2017) - Russenschuck, Stephan
Abstract : Purpose: The purpose of this paper is to establish the mathematical foundations of magnetic measurement methods based on translating-coil and rotating-coil magnetometers for accelerator magnets and solenoids. These field transducers allow a longitudinal scanning of the field distribution, but require a sophisticated post-processing step to extract the coefficients of the Fourier–Bessel series (known as pseudo-multipoles or generalized gradients) as well as a novel design of the rotating coil magnetometers. Design/methodology/approach: Calculating the transversal field harmonics as a function of the longitudinal position in the magnet, or measuring these harmonics with a very short, rotating induction-coil scanner, allows the extraction of the coefficients of a Fourier–Bessel series, which can then be used in the thin lens approximation of the end regions of accelerator magnets. Findings: The extraction of the leading term in the Fourier–Bessel series requires the solution of a differential equation by means of a Fourier transform. This yields a natural way to de-convolute the measured distribution of the multipole content. The author has shown that the measurement technique requires iso-parametric coils to avoid interception of the longitudinal field component. The compensation of the main signal cannot be done with the classical arrangement of search coils at different radii, because no easy scaling law exists. A new design of an iso-perimetric induction coil has been found. Research limitations/implications: In the literature, it is stated that the pseudo-multipoles can be extracted from field computations or measurements. While this is true for computations, the author shows that the measurement of the field harmonics must be done with iso-parametric coils because otherwise the leading term in the Fourier–Bessel series cannot be extracted. Practical implications: The author has now established the theory behind a number of field transducers, such as the moving fluxmeter, the rotational coil scanner and the solenoidal field transducer. Originality/value: This paper brought together the known theory of the orthogonal expansion method with the methods and tools for magnetic field measurements to establish a field description in accelerator magnets.